Challenges and opportunities for the development of a cold hardy citrus industry in florida panhandle - Martini, Xavier; Andersen, Peter (EDIS, 2018)
Cold hardy citrus have long history in north Florida and nearby states. After being “Satsuma Capital of the World” in the 20’s, North Florida cold hardy citrus production declined and was mostly eliminated after World War II. The relatively mild winter temperatures during the last three decades and the development of microjet irrigation in early 90’s to reduce the effects of freeze have led to a resurgence of interest in cold hardy citrus in north Florida. Currently, satsumas account for great majority of the new commercial citrus in north Florida. There is an urgent need to diversify fresh market citrus in north Florida to include varieties that ripen from September thru December. In this article, we detail cold hardy citrus varieties available for North Florida, and the challenges and opportunities associated with each of them. We also reviewing the different insect pests present in North Florida citrus grove. Finally, we present data on the population dynamic of the Asian citrus psyllid in backyard citrus of North Florida.